2014
DOI: 10.1080/1359432x.2014.892480
|View full text |Cite
|
Sign up to set email alerts
|

How to get radical creative ideas into a leader’s mind? Leader’s achievement goals and subordinates’ voice of creative ideas

Abstract: In the present research we investigated when and why leaders tend to oppose or adopt radical creative ideas voiced by their subordinates. In a field study (Study 1, N = 127) we showed that leaders' performance goals were positively related to their tendency to oppose radical creative ideas, whereas leaders' mastery goals were positively related to their tendency to adopt them. We replicated these findings in an experimental study (Study 2, N = 90), in which we showed that performance goal leaders were more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 87 publications
(125 reference statements)
4
77
1
4
Order By: Relevance
“…We zullen allereerst ons onderzoek bespreken dat laat zien dat performancedoelen en masterydoelen van leidinggevenden een verschillend effect hebben op hoe leidinggevenden omgaan met aangedragen creatieve ideeën (Sijbom, Janssen & Van Yperen, 2013;2015a;2015b). Daarna zullen wij studies laten zien die de onderliggende processen blootleggen en daarmee de vraag beantwoorden waarom leidinggevenden met performancedoelen en masterydoelen verschillend reageren (Sijbom et al, 2015a;2015b).…”
Section: Resultatenunclassified
See 3 more Smart Citations
“…We zullen allereerst ons onderzoek bespreken dat laat zien dat performancedoelen en masterydoelen van leidinggevenden een verschillend effect hebben op hoe leidinggevenden omgaan met aangedragen creatieve ideeën (Sijbom, Janssen & Van Yperen, 2013;2015a;2015b). Daarna zullen wij studies laten zien die de onderliggende processen blootleggen en daarmee de vraag beantwoorden waarom leidinggevenden met performancedoelen en masterydoelen verschillend reageren (Sijbom et al, 2015a;2015b).…”
Section: Resultatenunclassified
“…Daarna zullen wij studies laten zien die de onderliggende processen blootleggen en daarmee de vraag beantwoorden waarom leidinggevenden met performancedoelen en masterydoelen verschillend reageren (Sijbom et al, 2015a;2015b). Tot slot zullen wij onderzoek presenteren waarin condities zijn onderzocht waaronder met name leidinggevenden die performancedoelen nastreven meer effectief gedrag kunnen vertonen (Sijbom et al, 2015a;2015b).…”
Section: Resultatenunclassified
See 2 more Smart Citations
“…Over the past years, there has been growing scholarly interest in exploring factors that affect managers' reactions to voice. Studies have shown that voice frequency (e.g., Seibert, Kraimer, & Crant, 2001), the attributes of people involved (the voicing employee and the manager; e.g., Fast, Burris, & Bartel, 2014;Sijbom, Janssen, & Van Yperen, 2015a, 2015b, and the attributes of the voice message (e.g., Burris, 2012) affect managers' reactions to voice.…”
Section: General Introductionmentioning
confidence: 99%